2013
DOI: 10.1088/0964-1726/22/6/065005
|View full text |Cite
|
Sign up to set email alerts
|

Damage localization in composite laminates based on a quantitative expression of anisotropic wavefront

Abstract: In this paper, according to the disperse curve of composite laminates in a low frequency domain, a quantitative relation between anisotropic wavefront and propagation direction is proposed to reveal the direction dependency of Lamb wave propagation in composite laminates. This relation is described by a concise analytic expression, which can effectively incorporate anisotropic wave propagation into damage identification and reasonably determine the time-of-flight (ToF) of the Lamb wave. The reliability and app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 36 publications
(47 reference statements)
0
26
0
Order By: Relevance
“…Sparse piezoelectric sensor arrays have been studied for detection of composite damage in structural health monitoring (SHM) type setups [7,8]. These prior studies have shown that sparse sensor arrays have promise for locating damage regions in composites using a small number of sensors, but may be limited in ability to size and characterize damage.…”
Section: Introductionmentioning
confidence: 99%
“…Sparse piezoelectric sensor arrays have been studied for detection of composite damage in structural health monitoring (SHM) type setups [7,8]. These prior studies have shown that sparse sensor arrays have promise for locating damage regions in composites using a small number of sensors, but may be limited in ability to size and characterize damage.…”
Section: Introductionmentioning
confidence: 99%
“…According to equations (14) and (15), the damage indicators are basically a sum of terms, each one associated with one variable (sensor-time in the case of unfolded matrix), called contributions. Once a damage has been detected because the indices (Q and T 2 -statistics) take abnormal values, finding the elements of the signal x i which are mainly providing these values (highest contribution), means identifying the sensors, or more specifically, the wave propagation path that was more affected by the damage.…”
Section: Generalized Contribution Plots In Multiway Principal Componementioning
confidence: 99%
“…PCA modeling essentially consists of calculating the projection matrix P for each phase (equation 5), which offers a better and dimensionally reduced representation of the original data X und . Matrix P, renamed P m , will be considered as the model of the undamaged structure, besides the damage statistics by each trial Q und and T 2 und from equations (14) and (15) will be used in the diagnosis as illustrated in Figure 2.…”
Section: Pca Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Time-of-flight (ToF)-the time taken by the ultrasonic pulse to travel from an actuator to a sensor-is a feature extracted from the scattered signals that are widely used in target localization [12,13]. Many studies have reported the successful application of ToF-based methods for target localization [1,4,14,15], but the accuracy is affected by ToF measurement errors.…”
Section: Introductionmentioning
confidence: 99%